Application of horizontal slice method on geosynthetics reinforced slope - Lee, Sharon Fung Choo (Universiti Malaysia Sarawak, UNIMAS, 2013)
The purpose of the study is to apply the Horizontal Slice Method (HSM) in slope stability analysis for slope reinforced with geotextile. This is a new method which can resolve the problem of direct influence of reinforcement on the inter-slice forces encountered in the Vertical Slice Method. This new method had been used in past researches done by Nouri et al. (2006) and Taib & Craig (2007). The results from their research had shown close values with the conventional methods. The simple formulation of the HSM comprising of (2N+1) unknowns and (2N+1) equations suggested by Shahgholi et al. (2001) were used in this study. Factors contributing to slope instability were identified as the factors would influenced the formulating of the equations for vertical forces and horizontal forces in the slope. The factors were slope geometry, soil properties, groundwater condition and configuration of reinforcement. A spreadsheet had been designed using Microsoft Excel 2007. There are four sections in the spreadsheet. Namely the data input, data generation, data analysis and result. With the trial and error method, the factor of safety is found when the equilibrium of the horizontal forces for the whole wedge of slope is achieved. Validation work using Plaxis Version 8.2 was carried out to test the reliability of the spreadsheet. Six slopes had been designed for the validation work. The deviations between the factors of safety from Plaxis and the factors of safety from spreadsheet were ranged from 0.6 % to 3.27 %. The deviations were considered low, thus the HSM can give values close to the existing software. The results from the spreadsheet had same pattern as the results from Plaxis Version 8.2. This also confirmed that the spreadsheet had been prepared with no error.